RANTAI PENJELAS KONFLIK-KONFLIK AGRARIA YANG KRONIS, SISTEMIK, DAN MELUAS DI INDONESIA - Rachman, Noer Fauzi (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Abstract: The article offers an framework to identify causes, effects, perpetuating conditions, and structural roots of agrarian conflicts. Systemic agrarian conflicts were defined as everlasting contradictory claims on who had the rights over access to lands, natural resources, and territories between rural community and concession holders in the business of plantation, forestry, mining, infrastructure, etc. The conflicting claims are perpetuated by significant efforts to delegitimize the existence of others’ claims. Being different from various mainstream analysis promoting global market as opportunity, I prefer to use what Ellen M. Wood notion of “market-as-imperative”. Using the illustration of the expansion of oil palm plantation in Indonesia, the article shows the consequence of global capitalist markets to the emergence of the agrarian conflicts. Keywords: agrarian conflicts, market, agrarian capitalism.